Epizootic Situation in the Crimean Federal District as Follows from Epidemiological Survey Results, 2014 - A. Yu. Popova; E. B. Ezhlova; Yu. V. Demina; L. I. Shaposhnikova; I. L. Evstaf’Ev; N. N. Tovpinets; E. S. Kotenev; A. S. Volynkina; Ya. V. Lisitskaya; I. V. Samarina; O. A. Belova; N. V. Tsapko; et al. (Problems of Particularly Dangerous Infections, 2015)
The territory of the Crimean Peninsula is an endemic one as regards various natural-focal infections. The paper contains the data on epizootiological survey of 8 administrative regions of the Crimean Federal District (CFD). Carried out has been small mammals and Ixodidae ticks census. Identified is their species composition. Performed have been the field samples collection and laboratory studies for the presence of bacterial and viral infection agents. Established is the fact that H. marginatum is a dominating species among the ticks, collected during the spring season, while the house mouse prevails among the small mammals. As for the autumn collection of samples, the dominating species are H. punctata and common vole, respectively. Laboratory investigation results indicate the circulation of the agents of Ku fever, tick-borne spotty fever, Ixodidae tick-borne borreliosis, human granulocytic anaplasmosis, monocytic ehrlichiosis, hemorrhagic fever with renal syndrome and leptospirosis. Территория Крымского полуострова является эндемичной по многим природно-очаговым инфекциям. В работе представлены результаты эпизоотологического обследования 8 административных районов Крымского федерального округа (КФО). Осуществлен учет численности мелких млекопитающих и иксодовых клещей, определен их видовой состав, проведен отбор проб полевого материала и лабораторные исследования на наличие возбудителей бактериальных и вирусных инфекций. Установлено, что доминирующим видом клещей в сборах весной является H. marginatum , доминирующим видом мелких млекопитающих - мышь домовая. В сборах осенью преобладают H. punctata и полевка обыкновенная. Результаты лабораторного исследования полевого материала свидетельствуют о циркуляции на территории КФО возбудителей лихорадки Ку, клещевых пятнистых лихорадок, иксодового клещевого боррелиоза, гранулацитарного анаплазмоза человека, моноцитарного эрлихиоза человека, геморрагической лихорадки с почечным синдромом и лептоспироза.